Curricular policy and social exclusion in the context of marketing society (Revista Contexto & Educação, 2026)
The curriculum and exclusion in the public school of the consumer society is an important problem to be put on the agenda, because it helps to understand how institutionalized discrimination of majorities occurs. With an interest in deepening this knowledge, this study sought to develop an argument around the neoliberal discourse in relation to educational practices, within the public school. To this do so, the investigation was based on Bauman's arguments (2008, 2015); Hall (2016, 2019); Charaudeau (2005, 2016); Silva (1999, 2013, 2014, 2020); Gentili (2013, 2015); Torres Santomé (2003, 2013a, 2013b); Hooks (2019) and others. The research is of qualitative approach, exploratory, descriptive and argumentative, of an applied nature. The study has as corpus of discourse analysis the circuit of culture.  It is infers that the public school is involved in the dilemma of the teaching of cultural knowledge in contrast to a curriculum configured in terms of market logic, which causes exclusion of the majorities by the bias of hegemonic curricular practices.
Keywords: Neoliberalism; Curriculum; Exclusion; Circuit of Culture